The Significant Expressions of Distrust and Pessimism to the Police in Franz Kafka’s Give It Up! - Dewangga, Diandra Parta Wisnu; Wijaya, Kusuma; Shamad, Dzil Fikris; Ananta, Bintang Ryan; Marharendra, Ahmad Maulana; Pasopati, Rommel Utungga (PT. Gudang Pustaka Cendekia, 2024)
This paper investigates matters of district and pessimism to the police in Franz Kafka’s flash fiction entitled Give It Up!. The story is about a walker who gets lost on a town street and then asks a policeman to find the route to his destination. Unexpectedly, the policeman told the man to give up looking for the path while turning away and laughing. This story reflects the author's expression of distrust then leads to a state of pessimism either as a philosophical doctrine or as a psychological mentality. In analysis through qualitative method, the figure of the police is an analogy of how the attitude of distrust emerged and developed into a form of pessimism especially to public apparatus. In conclusion, distrust and pessimism are not ex nihilo, but such reaction of any ignorance from public apparatus to any civilian.